2022
DOI: 10.1002/pchj.598
|View full text |Cite
|
Sign up to set email alerts
|

Culture–sex interaction in self‐report empathy: The theory and meta‐analyses

Abstract: Empathy is sharing and understanding others' emotions. Recently, researchers identified larger Western-Asian cultural differences in self-report empathy with females relative to males (i.e., the culture-sex interaction theory). Neglecting this phenomenon, previous researchers focused on identifying the cultural impact on empathy per se and reported divergent results. This meta-analysis aims to reveal the heterogeneity of the earlier publications and decode the heterogeneity as per the culture-sex interaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The enhanced prominence of psychopathy in males vs. females has been meta-analytically validated, even after controlling for other personality traits (Muris et al, 2017;Sanz-García et al, 2021). Sex-empathy interaction is far more intricate, as current evidence suggests that sex differences may (or may not) arise from a complex interaction between methodological (self-report vs. experimental tasks), biological, and environmental factors (Konrath et al, 2011;Christov-Moore et al, 2014;Warrier et al, 2018;Abramson et al, 2020;Rochat, 2022;Zhao et al, 2022). Recent metaanalytical evidence also indicated that male subjects display enhanced cardiac interoceptive accuracy, despite findings being consistent with other interoceptive modalities (Prentice and Murphy, 2022).…”
Section: The Putative Confounding Role Of Alexithymia Age and Sexmentioning
confidence: 99%
“…The enhanced prominence of psychopathy in males vs. females has been meta-analytically validated, even after controlling for other personality traits (Muris et al, 2017;Sanz-García et al, 2021). Sex-empathy interaction is far more intricate, as current evidence suggests that sex differences may (or may not) arise from a complex interaction between methodological (self-report vs. experimental tasks), biological, and environmental factors (Konrath et al, 2011;Christov-Moore et al, 2014;Warrier et al, 2018;Abramson et al, 2020;Rochat, 2022;Zhao et al, 2022). Recent metaanalytical evidence also indicated that male subjects display enhanced cardiac interoceptive accuracy, despite findings being consistent with other interoceptive modalities (Prentice and Murphy, 2022).…”
Section: The Putative Confounding Role Of Alexithymia Age and Sexmentioning
confidence: 99%
“… 1 To date, researchers have observed the “culture–sex interaction effect” in studies of self-esteem ( 2 ), emotional processing ( 3 ), and interpersonal empathy ( 4 , 5 ). …”
mentioning
confidence: 99%